Green tea infusion prevents diabetic nephropathy aggravation in recent-onset type 1 diabetes regardless of glycemic control. (28th June 2021) - Ladeira, Luiz Carlos Maia; dos Santos, Eliziária Cardoso; Santos, Talita Amorim; da Silva, Janaina; Lima, Graziela Domingues de Almeida; Machado-Neves, Mariana; da Silva, Renê Chagas; Freitas, Mariella Bontempo; Maldonado, Izabel Regina dos Santos Costa
Abstract: Ethnopharmacological relevance: Green tea, traditionally used as antidiabetic medicine, positively affects the diabetic nephropathy. It was assumed that these beneficial effects were due to the hypoglycemiant capacity of the tea, wich reduces the glycemic overload and, consequently, the advanced glycation end products rate and oxidative damage. However, these results are still controversial, since tea is not always able to exert a hypoglycemic action, as demonstrated by previous studies. Aim: Investigate if green tea infusion can generate positive outcomes for the kidney independently of glycemic control, using a model of severe type 1 diabetes. Material and methods: We treated streptozotocin type 1 diabetic young rats with 100 mg/kg of green tea, daily, for 42 days, and evaluated the serum and tissue markers for stress and function. We also analyzed the ion dynamics in the organ and the morphological alterations promoted by diabetes and green tea treatment. Besides, we analyzed, by an in silico approach, the interactions of the green tea main catechins with the proteins expressed in the kidney. Results: Our findings reveal that the components of green tea can interact with the proteins participating in cell signaling pathways that regulate energy metabolism, including glucose and glycogen synthesis, glucose reabsorption, hypoxia management, and cell death by apoptosis. Such interaction reduces glycogen accumulation in the organ, and protects the DNA. These results also reflect in a preserved glomerulus morphology, with improvement in pathological features, and suggesting a prevention of kidney function impairment. Conclusion: Our results show that such benefits are achieved regardless of the blood glucose status, and are not dependent on the reduction of hyperglycemia. Graphical abstract: Image 1